Simple method for high purity acylated steryl glucosides synthesis. Issue 5 (27th August 2015) - Jäger, Sebastián N.; Mittelbach, Martin; Cabrera, Rodolfo; Labadie, Guillermo R.
Abstract : The present work covers an important gap in the field of analytic standards synthesis of the plants minor component, the acyl steryl glucosides (ASG). A simple and powerful procedure that allows the synthesis of different ASG has been introduced. The regioselective acylation of steryl glucosides on the C–6–OH of the glucose was produced using sym‐collidine and acyl chloride. The reaction was optimized analyzing the conditions to maximize the isolated yield of the monoacylated product. Practical applications: The identification and quantification of acyl steryl glucosides (ASG) and steryl glucosides (SG) is a difficult task and has become increasingly important in the food, oil and biodiesel industries. There is a lack of simple synthetic approaches to prepare ASG and commercial sources of those compounds as analytical standards are expensive and sometime do not have the required purity. In this paper we are introducing a simple, powerful and versatile procedure that allows the synthesis of different ASG in a rapid and efficient way, producing the products in high purity that will enable them to be use as standards. The present work covers an important gap in the field of analytic standards synthesis of the plants minor component, the acyl steryl glucosides (ASG). A simple and powerful procedure that allows the synthesis of different ASG has been introduced. Abstract : The present work covers an important gap in the field of analytic standards synthesis of the plants minor component, the acyl steryl glucosides (ASG). A simple and powerful procedure that allows the synthesis of different ASG has been introduced.